Self-Esteem dan Optimisme Hubungannya dengan Subjective Well-Being Remaja Panti Sosial Asuhan - Farhatunni’mah, Farhatunni’mah; Rahayu, Anizar (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study aims to determine the relationship between self-esteem and optimism with subjective well-being of adolescents in social care institutions in Jakarta. This study uses quantitative methods, with3 research instruments, namely subjective well-being based on Diener's theory (2009), self-esteembased on Tafarodi and Swann's theory (2001) and optimism based on Seligman (2008). The sampleof this study amounted to 158 adolescents. With the sampling technique using simple randomsampling. Data were collected by questionnaire and analyzed using the JASP 0.18.3.0 program forWindows. The results of this study using the bivariate correlation method show that there is asignificant relationship with a positive direction between self-esteem towards the subjective wellbeingofadolescentsinsocialorphanagesinJakartawithacorrelationcoefficient(r=0.560 p =<0.001 (<0.05)), there is a significant relationship with a positive direction between optimismtowards the subjective well-being of adolescents in social orphanages in Jakarta based on the resultsof the coefficient (r = 0.231 with p = 0.003 (<0.05)). Based on the results of the analysis using themultivariate Correlation enter method, the R value is 0.536 and R2is 0.288 with p = <0.001(<0.05)). This shows that there is a significant relationship between self-esteem and optimismtowards the subjective well-being of adolescents in social care institutions in Jakarta by 28.8%.Based on multivariate correlation stepwise, the contribution of self-esteem to the formation ofsubjective well-being is 28.7% while optimism contributes 0.1%.